Case management - Marnetoft, Sven-Uno (Rehabilitacija (Ljubljana), 2015)
In recent years, the interest in case management has increased more and more. Case management has traditionally been seen as a way of coordinating and distributing the community's resources efficiently. The primary aim of case management is to support people with various disabilities so that they have access to the resources that are needed for them to be able to live as independent a life as possible. Case management therefore focuses on what happens in day-to-day life scenarios such as health, work, and housing, family and leisure time. Some of the existing case management models have also become better known than others over the years. These are Assertive Community Treatment (ACT), the Brokerage Model and the Strengths Model. Some case management models are focused more on solving problems than on looking at the strengths of the individual and strengths in the community. All individuals have the capacity to grow, develop and recover. The Strengths Model stands out by virtue of its strong focus on the client's strengths rather than shortcomings and weaknesses, and on the fact that the client's self-determination is important as regards the specialisation of the rehabilitation process and the importance of the use of informal resources. The model also emphasises the importance of creating a good and reliable relationship with the client and of working out there in the society where the resources are available. During the rehabilitation process, the case manager has the task of mobilising the client's strengths, abilities and talents as well as the community's resources. Results from several Strengths Model case management studies support the effectiveness of the model. People involved in Strengths Model studies have lowered their sickness benefit levels, improved their social contacts, decreased their drug use, increased their working capacity, and improved their quality of life.
Keywords: Case Management; model Strengths; uporabniki rehabilitacije; viri; vodenje primera